Persepsi Masyarakat Transmigran Jawa di Daerah Paguyaman Provinsi Gorontalo Terhadap Kebijakan Transmigrasi Pada Masa Pemerintahan Soeharto - Hasan, Renol; Mohamad, Sutrisno; Malae, Andris K.; Latif, Fikriyanto R. (Dynamics of Rural Society Journal, 2023)
This study aims to determine the perceptions of the Javanese people in the Paguyaman Region of Gorontalo Province towards the transmigration policy during the Soeharto era. The research method used in this study is a qualitative method with a descriptive approach. Data collection was carried out using interview techniques and field observations. The results of the research show that the people were disappointed with several things regarding the transmigration program, especially regarding the government's promises at that time, which were not fully realized. There were several problems at the destination location that contributed to the transmigrant community's dissatisfaction with the program, including the government's promise that the location where the transmigrants would live was ready to be occupied and agricultural land was also ready to be worked on, but in reality, the location of the placement transmigrants is still the wilderness, and the promised agricultural land still had to be cleared of weeds. The transmigrant community felt that what the government had promised during socialization was still far from the community's expectations when they saw the placement locations first hand.